2006
DOI: 10.1002/j.1551-8833.2006.tb07568.x
|View full text |Cite
|
Sign up to set email alerts
|

Pilot‐scale study of Polyelectrolyte‐Enhanced UF for arsenic removal

Abstract: The removal of arsenic (As) from dilute aqueous solutions has become of greater interest as lower drinking standards are implemented. In polyelectrolyte‐enhanced ultrafiltration (PEUF), a cationic water‐soluble polyelectrolyte (poly‐diallyldimethylammonium chloride [QUAT]) binds the anionic arsenate species and is rejected by the membrane, which has a 10 kDa molecular weight cutoff (MWCO). In the research presented in this article, PEUF was used to treat water with As concentrations of 50–100 μg/L. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Further work demonstrated scale up in a continuous PEUF process achieving 94% arsenic removal from 50 ppb arsenic contaminated water, thus achieving the 10 ppb MCL standard for arsenic in drinking water [6]. The authors also reported analysis of the relative cost for purifying drinking water using PEUF and several traditional technologies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further work demonstrated scale up in a continuous PEUF process achieving 94% arsenic removal from 50 ppb arsenic contaminated water, thus achieving the 10 ppb MCL standard for arsenic in drinking water [6]. The authors also reported analysis of the relative cost for purifying drinking water using PEUF and several traditional technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Methods: Polyelectrolyte recovery experiments were conducted by adding divalent metal chloride solution to synthetic PDADMAC-arsenate complex solutions to precipitate arsenic oxyanions from the solution. Initial arsenic concentrations of 100 ppb were selected to be compatible with the levels of arsenic in the retentate from the continuous PEUF process [6]. Parameters varied include the temperature, the ratio of PDADMAC:arsenic, pH, and the degree of supersaturation.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of PEUF with regard to anion retention has also been examined previously by a number of studies. For instance, chromate retention using ethoxylated polyethyleneimine, poly(diallyldimethylammonium) chloride, chitosan, and pectin as chelating polyelectrolytes, nitrate retention using poly(dimethylaminecoepichlorohydrin), poly(diallyldimethylammonium) chloride, and poly(dimethylamine-co-epichlorohydrin-co-ethylenediamine), and removal of anionic species such as arsenic and perchlorate, by employing poly(diallyldimethylammonium) chloride as the complexing agent, have been formerly appraised by several scientific explorations [20][21][22][23][24][25][26][27][28][29]. Meticulous retrospection of archival literature however manifests the parochial availability of studies dealing with the application of PEUF for bringing about effective retention of dyes from colour-contaminated effluent streams.…”
mentioning
confidence: 99%